Orbit and Clock Determination of QZS‐1 Based on the CONGO Network. Issue 1 (20th March 2013) - Steigenberger, P.; Hauschild, A.; Montenbruck, O.; Rodriguez‐Solano, C.; Hugentobler, U.
ABSTRACT: QZS‐1 is the first satellite of the Japanese Quasi‐Zenith Satellite System (QZSS) launched in September 2010. Five stations of the Cooperative Network for GIOVE Observation (CONGO) are able to track the QZSS L1, L2, and L5 navigation signals. Together with the GPS observations of these stations, QZS‐1 orbit and clock parameters were estimated. Various orbit parameterizations were tested and a sub‐meter accuracy of the best orbits could be achieved. Differences of orbits obtained from various linear combinations are on the decimeter level and differential code biases are on the few nanosecond level. Short periodic variations with a peak‐to‐peak amplitude of about 4 cm were detected in the QZS‐1 clock estimates. Three time intervals with different periods of 13.6 – 15.5 minutes could be identified. Three way carrier phase analysis confirmed the presence of these variations. The origin of these periodicities is considered to be an artifact of the time keeping system. Copyright © 2013 Institute of Navigation.